Substrates and containers influence the growth of Campomanesia phaea (O. Berg. Landrum) seedlings, an endangered Atlantic Rainforest species - Santoro, Marcelo Brossi; Gomes, Juliana Aparecida Souza; Brogio, Bruna do Amaral; Jacomino, Angelo Pedro; Silva, Simone Rodrigues da (Acta Scientiarum. Agronomy, 2023)
Native to the Brazilian Atlantic Rainforest, cambuci fruits can be consumed either in natura or in the processed form, and cambuci trees can be used to recover degraded areas. However, studies regarding cambuci germination and seedling development are scarce. The main aim of this study was to understand how different substrates and containers influence the growth of cambuci seedlings. To this end, two experiments were conducted: five different substrates were tested in the first experiment, and based on the multivariate analysis of the first experiment, the effect of combination of the best-performing substrates and three commonly employed plant growth containers on seedling development was investigated. Overall, good quality cambuci seedlings were obtained when they were grown in the commercial pine bark substrate and peat and perlite mixture in a 260 cm3 container.